THE MAIN ASPECTS OF MENOPAUSAL METABOLIC SYNDROME - Talmasovna, Kayumova Dilrabo (International Journal of Psychosocial Rehabilitation, 2020)
ObjectiveThe aim of the study was to conduct a comprehensive assessment of women's health in the late reproductive, peri- and postmenopausal periods to determine the frequency, clinical course, as well as the prerequisites for the development of climacteric syndrome (CS) and metabolic syndrome (MS). We can state that the main triggers are hyperinsulinemia, insulin resistance and visceral obesity, which contribute to dyslipidemia, oxidative stress, inflammation, altered coagulation and atherosclerosis observed during menopause. Timely undetected and untreated metabolic disorders can adversely affect the duration and quality of life of women.Materials and methods:Examination of 1484 women aged 35-70 and conducting general clinical, special gynecological, biochemical (lipid spectrum with calculation of the atherogenic index of plasma, glucose level in blood serum), as well as conducting an assessment scale of Kupperman menopausal index for the presence of CS with determination of its severity, as well as determination MS frequencies. Results:It was determined that CS was observed in 93.3% of the examined women against a background of aggravated somatic and gynecological pathology. This led to the development of menopausal syndrome in 30.6% of women, and most often it was observed in perimenopausal women (45-54 years old) - in 33.9% and almost every second woman (55.4%) with moderate grade CS gravity. Conclusion:The presence of MS indicators significantly aggravates the course of menopause, causing high comorbidity and the development of the clinic of CS.